2000
DOI: 10.1056/nejm200007133430203
|View full text |Cite|
|
Sign up to set email alerts
|

Validity of a Set of Clinical Criteria to Rule Out Injury to the Cervical Spine in Patients with Blunt Trauma

Abstract: A simple decision instrument based on clinical criteria can help physicians to identify reliably the patients who need radiography of the cervical spine after blunt trauma. Application of this instrument could reduce the use of imaging in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
535
3
36

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 1,163 publications
(584 citation statements)
references
References 35 publications
10
535
3
36
Order By: Relevance
“…In fact, this study showed an association of 100% between cervical spine injuries and head injury. Moreover, the literature reports an average incidence of 50% of injuries to other organs associated with cervical spine injuries 12,16 and in the present study we observed an association between cervical spine injury and injuries to other organs in 100% of cases. We also found that the severity of the victims (as measured by ISS, and TRISS RTS) was higher among those who had cervical lesions at CT.…”
Section: Results Results Results Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…In fact, this study showed an association of 100% between cervical spine injuries and head injury. Moreover, the literature reports an average incidence of 50% of injuries to other organs associated with cervical spine injuries 12,16 and in the present study we observed an association between cervical spine injury and injuries to other organs in 100% of cases. We also found that the severity of the victims (as measured by ISS, and TRISS RTS) was higher among those who had cervical lesions at CT.…”
Section: Results Results Results Resultssupporting
confidence: 73%
“…Hence the great importance of early and accurate diagnosis of lesions of the spine and cervical spinal cord in victims of blunt trauma 11,12 . Several diagnostic methods are used to identify such lesions, from physical examination to more sophisticated imaging tests, such as computed tomography (CT) and magnetic resonance imaging (MRI) 5,8,12 , CT being the most used feature, allowing to Pinheiro Pinheiro Pinheiro Pinheiro Pinheiro Diagnostic value of tomography of the cervical spine in victims of blunt trauma characterize the presence or absence of injury to the cervical spinal column in most cases 11,12 .…”
Section: Results Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of these studies were done in the obtunded or altered patient; few address the dilemma of cervical spine clearance in the awake and alert patient with ongoing cervical tenderness [6,7]. The EAST and NEXUS guidelines recommend flexion extension films for the awake and alert patient with continued cervical tenderness after negative plain films or CT scans [2,19,20]. The algorithms mandate that the flexion extension films be adequate and negative however those terms are not specifically defined.…”
Section: Discussionmentioning
confidence: 99%